EXPLORING THE ANTIBACTERIAL POTENTIAL OF C. GIGANTEA IN THE GEOTHERMAL AREA OF IE JUE: A BIOINFORMATICS APPROACH - NINGSIH, DIANA SETYA; IDROES, RINALDI; KHAIRAN, KHAIRAN; JAKFAR, SUBHAINI; SUNDARI, IIN; DIANSARI, VIONA; FITRIANI; HANDAYANI, AFRI; AQIFAH, INAS (International Journal of Applied Pharmaceutics, 2024)
Objective: The Aceh geothermal region offers an enticing possibility for research into prospective contributions to the medical field, particularly in dentistry. C. gigantea, a hardy plant that can withstand high temperatures, grows in this area. Methods: This plant contains a large number of secondary metabolites that are known to be useful in herbal medicine. However, there has not been much research done in this field of oral health; thus finding the plant's potential will require a cheap detecting tool. One method for this investigation is molecular docking, which is a part of bioinformatics. Molecular docking is a method used to examine how drugs interact with proteins, such as the proteins from the halitosis-related bacteria Porphyromonas gingivalis (P. gingivalis). Results: In this study, computational technologies will be used to find antibacterial properties. In particular, the antibacterial effects of chemical compounds from Biduri leaves (C. gigantea) discovered in the Ie Jue geothermal zone are examined. The study uses molecular docking to compute the interactions of the five Biduri metabolites: lupenyl acetate, α-amyrin, phytol, β-amyrenyl acetate, and methyl ester with the Kgp protein in P. gingivalis. Conclusion: The data show a range of binding affinities, with α-amyrin showing the most promising results with a binding affinity of -9.7 kcal/mol for Kgp protein. According to this study, P. gingivalis, the bacteria that cause halitosis, may be susceptible to the antibacterial effects of C. gigantea leaves.